PENGAWASAN BIRO PENYELENGGARA UMRAH DI KOTA PEKANBARU - Kanzularas Iso Dina; Zulkarnaini " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
Umrah is a holy activity whose implementation aims to achieve His blessing. The implementation of Umrah worship has been regulated in the Regulation of the Minister of Religion (PMA) Number 8 of 2018 concerning the implementation of Umrah worship. The implementation of the Umrah pilgrimage has long been an important issue that has attracted a lot of public attention. This attention mainly revolves around the problem of implementation which is considered to be problematic at the national level. From public complaints regarding Umrah administration to fraud cases regarding Umrah organizing bureaus that make people ask how the Ministry of Religion supervises the organizing bureau. The method used in this research is qualitative, the data collection techniques used are interviews, observation and documentation. Sources of data used in this study include primary data and secondary data, the location of the study was conducted at the Ministry of Religion, Pekanbaru City. The research informants in this study were the Umrah Organization Section, Travel Parties and Umrah Participants. The theoretical concept used in this research is the theory of supervision according to Hasibuan which consists of standard setting, measuring the implementation of activities, comparing, taking corrective action. From the research results, that the supervision of the Umrah organizer in Pekanbaru City, the supervision of the Umrah organizer in Pekanbaru City is well but it’s still there factors that hinder the supervision of the Umrah organizer in Pekanbaru City are communication and the absence of a budget.Keyword : Supervision, organizer bureau